4CPS-134 Optimisation of denosumab prescription in osteoporosis patients. (23rd March 2022) - Salom, C; Bejarano, F; Campabadal, C; Conde, S; Castillo, L; Marco, N; Sanjuan, A; Sacanella, I; Suñer, H; Canadell, L
Abstract : Background and importance: Bisphosphonates should be the first choice for osteoporosis treatment, with lower cost and no less benefit than denosumab. Aim and objectives: To evaluate the indication for treatment with denosumab and to develop proposals for optimising osteoporosis treatment. Material and methods: Cross-sectional study in a primary care area (8 centres). Data from the ECAP digital medical record of denosumab-treated patients during January 2020 were reviewed by the Pharmacy Service. Variables: demographic (age and sex), diagnosis, bone mineral density (BMD) and previous fractures, indication, previous treatment and adherence. Results: A total of 394 denosumab-treated patients, aged 74.9 ± 9.6 years, 92.6% women, were included. BMD T-score was ≤–2.5 (indicative of osteoporosis) in 48.3% of men and 64.1% of women, while it was >–2.5 in 6.9% of men and 14.8% of women. There was no densitometric test in the remaining patients. The most prevalent previous fracture in men was hip fracture (31%), while previous fracture was not present in most women (49.6%). Other fractures in men: 27.6% none, 24.1% vertebral, 17.3% ≥2 vertebral. In women: 16.7% ≥2 vertebral, 13.7% vertebral, 13.4% hip, 6.6% peripheral. Therefore, 80.8% of patients actually suffered from osteoporosis, while 19.2% had no true diagnosis. Osteoporosis patients receiving denosumab without a clear indication were 47.1%. Some 63% received prior treatment and 72.6% were adherent. Regarding those with an indication, 54.9% were due to ≥2 previous vertebral or hip fractures, 21.3% to adverse effects or poor adherence to bisphosphonates, 7.9% to chronic corticosteroid therapy, 7.4% to incident hip fracture or increased risk of fracture with age between 65 and 70 years, 5% to digestive alteration that contraindicates the use of therapeutic alternatives, and finally 3.5% to glomerular filtration <35 mL/min/m 2 . Denosumab should be withdrawn in 22% of patients and it should be changed to bisphosphonate in 25.1%, thus leading to a theoretical €75 100 annual saving. Conclusion and relevance: Denosumab should be withdrawn or replaced in 47.1% of patients. The proposals of the clinical pharmacist contribute to safe drug use and health system efficiency. It would be necessary to know the final implementation of the proposals by rheumatologists, which were pending due to the COVID-19 pandemic. References and/or acknowledgements: Conflict of interest: No conflict of interest